2021
DOI: 10.1080/09500693.2021.1936271
|View full text |Cite
|
Sign up to set email alerts
|

Using dialogic interventions to decrease children’s use of inappropriate teleological explanations

Abstract: A belief in teleology is often suggested to be a barrier in children's science education. Many studies have catalogued children's use of teleological explanations, but fewer have developed approaches to tackle children's use in scientific contexts. This paper reports two studies that utilised dialogic interventions alongside Concept Cartoons to do just that. Study 1 (5-to 7-yearolds, n = 54) addressed teleological explanations for natural phenomena (e.g., snow or rainbows) and Study 2, (9-to 10-year-olds, n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This finding is important because group SA−CMK− received the same information regarding key concepts during the intervention phase (e.g., through a simulation and a list of all key concepts) and even received more subject‐specific knowledge when the intervention groups had the intervention on conditional metaconceptual knowledge; yet students in the group SA−CMK− used fewer key concepts than the groups receiving one or both interventions. Thus, our findings demonstrate that while solely teaching subject‐specific knowledge may improve students' conceptual knowledge to some extent, the improvement is much greater when intuitive conceptions are also explicitly addressed (see also Aptyka et al, 2022; Colton et al, 2018; Halls et al, 2021; Nehm et al, 2022; Pickett et al, 2022).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…This finding is important because group SA−CMK− received the same information regarding key concepts during the intervention phase (e.g., through a simulation and a list of all key concepts) and even received more subject‐specific knowledge when the intervention groups had the intervention on conditional metaconceptual knowledge; yet students in the group SA−CMK− used fewer key concepts than the groups receiving one or both interventions. Thus, our findings demonstrate that while solely teaching subject‐specific knowledge may improve students' conceptual knowledge to some extent, the improvement is much greater when intuitive conceptions are also explicitly addressed (see also Aptyka et al, 2022; Colton et al, 2018; Halls et al, 2021; Nehm et al, 2022; Pickett et al, 2022).…”
Section: Discussionmentioning
confidence: 54%
“…However, the aforementioned studies did not investigate the individual effects of different instructional approaches to deal with student conceptions, leaving the question of how best to address intuitive conceptions. Other studies have indicated positive effects of instructional approaches that address students' conceptions such as refutation texts (Pickett et al, 2022), clarifications of misconceptions (Aptyka et al, 2022), discussions about common misconceptions using active learning approaches (Colton et al, 2018), group discussions about styles of scientific explanations (Halls et al, 2021), or direct challenges to intuitive thinking (Wingert et al, 2022). However, no rigorous experimental intervention study exists yet that investigates the effectiveness of specific metaconceptual approaches that are based on self-regulated learning and metacognition and directly address students' intuitive conceptions.…”
Section: Instruction On Conditional Metaconceptual Knowledgementioning
confidence: 99%
See 1 more Smart Citation